Avaliação da ocorrência de hanseníase entre os contatos intradomiciliares de pacientes diagnosticados em 2012 no Município de João Pessao/PB - Trindade, Luciana Cavalcante (2015)
Leprosy remains a public health problem in Brazil. Despite the improvement in epidemiological indicators, case detection rate remains high in the country. Studies show that household contacts of leprosy patients are the group with the highest risk of developing the disease and the monitoring of contacts is among the priority actions for early diagnosis and control of disease in the country. General Objective: To evaluate the occurrence of leprosy among household contacts of patients diagnosed in 2012 in João Pessoa / PB. Method and sample: Observational study, crosssectional, whose population were household contacts of new leprosy cases diagnosed in 2012 in João Pessoa / PB. Research assistants conducted household interviews - using a pre-tested form containing the variables of interest - and they did physical examination of contacts, to search for lesions suggestive of leprosy and BCG scar. A descriptive analysis of all variables was made; the association between two qualitative variables was verified by the chi-square test; logistic regression models were applied to investigate possible risk factors; we adopted the 0.05 significance level. All ethical aspects were respected. Results: One hundred and ninety contacts related to 72 index cases were interviewed. The prevalence rate of leprosy cases among contacts was 9/191 people (4.7%). In the socioeconomic and demographic data, there was a female predominance (61.1%); the median age was 33 years; most were single (59.5%); nearly 85% had some degree of education; the most common race was white (52.6%); family income was between one and five minimum wages in almost 95% of households; the most common occupation was student (33.7%). In assessing contacts diagnosed with leprosy, leprosy borderline predominated (62.5%), multibacillary (87.5%) and the disability grade one (50.0%) were most common. On four occasions, the operational form was equal to the case and the contact. In the other, the contact showed a multibacillary, while the index case was paucibacillary. Sixty-three percent of the contacts mentioned were invited to attend the health unit, 52.1% attended and 52.4% were instructed to receive the BCG. The majority had some vaccination scar, and 73.1% had only one. Half of contacts who developed the disease had a BCG scar and the other half did not have any. Together, the factors associated with the risk of developing leprosy were the absence of vaccination with BCG and the chronic use of medications. Discussion and Conclusions: The incidence of leprosy among contacts was high and it was similar to that found by other authors. Failures were noted in the surveillance activities by health facilities. The control measures of contacts established by the Ministry of Health and the compatible strategies with local endemic variations and education of the population may bring an adequate coverage of contacts, improving detection and preventing disability and reducing the stigma related to diagnosis lateonset disease.